ANALISIS PENGARUH KEPUASAN PASIEN TERHADAP KUALITAS PELAYANAN RESEP DI APOTEK INSTALASI FARMASI BADAN RUMAH SAKIT DAERAH LUWUK KABUPATEN BANGGAI - Dyah Nurfitri Maharani; Alwiyah Mukaddas; Indriani Indriani (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2016)
Pharmacy is one place of the pharmaceutical care with aims to practice pharmacy by pharmacists and pharmaceutical supply distribution to the public. One of the indicators use to evaluate the quality of care in pharmacies was to measure the level of customer satisfaction.This research is aimedto find out the impact of patient satisfaction towards the quality of prescription service in dispensary of pharmacy installation in Public Hospital of Luwuk, Banggai regency which is related with five dimension of quality service, which are; tangible, reliability, responsiveness, assurance and empathy. This research was conducted used sampling method called accidental sampling using questioner with likert scale. The data was analyzed using doubled linear regression method with the total of 110 respondent. The result from these respondent showed tangible, reliability, responsiveness, Assurance and empathyvariablewhich significantly affected the satisfaction of patient, with significance score of 0,000 (P value< 0,05). Determination coefficient resulted is 0,482 which mean that the satisfaction level of patient towards the five variables is 48,2%.